2018
DOI: 10.21873/anticanres.12346
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Therapy for Angiosarcoma of the Scalp: Total Scalp Irradiation and Local Irradiation

Abstract: Abstract. Angiosarcoma, a rare cutaneous malignancy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 23 publications
1
37
1
Order By: Relevance
“…Previous studies reported that a total dose of 70 Gy in 35 fractions was typically delivered to patients with angiosarcoma of the scalp that is highly malignant and associated with a very poor prognosis owing to distant metastases at an early stage [ 1 5 ]. Accordingly, it is important to reduce the radiation damage to the normal brain tissue occurring because of a higher prescription dose in such cases than in other TSI cases, such as cutaneous lymphoma and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that a total dose of 70 Gy in 35 fractions was typically delivered to patients with angiosarcoma of the scalp that is highly malignant and associated with a very poor prognosis owing to distant metastases at an early stage [ 1 5 ]. Accordingly, it is important to reduce the radiation damage to the normal brain tissue occurring because of a higher prescription dose in such cases than in other TSI cases, such as cutaneous lymphoma and squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Angiosarcoma of the scalp is a skin malignancy, which often shows local recurrence [ 1 , 2 ]. Radiation therapy is one of the most important treatment approaches for angiosarcoma of the scalp, and previous studies have reported about local control of this malignancy via total scalp irradiation (TSI) [ 3 5 ]. TSI has historically been associated with technical and dosimetric challenges because of the complicated shape of the target region and the close proximity of the scalp to the organs at risk (OARs), such as the brain and eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement of the scalp and calvarium is seen in conditions such as squamous cell carcinoma, angiosarcoma, lymphoma, and melanoma. 9 Infrequently, widespread involvement requires total scalp irradiation. This is more common in adults than in children.…”
Section: Discussionmentioning
confidence: 99%
“…Pre- or post-operative RT may be used less frequently in these groups, and this may have positively contributed to the LFRS in the population that did not receive RT. Even within high risk histologies, angiosarcomas are consistently shown to be highly malignant with high LR and DR rates and often receive RT as part of their treatment plan [15-17]. Our population contained a high percentage of angiosarcomas as compared to other STS sites [15].…”
Section: Discussionmentioning
confidence: 99%
“…Even within high risk histologies, angiosarcomas are consistently shown to be highly malignant with high LR and DR rates and often receive RT as part of their treatment plan [15-17]. Our population contained a high percentage of angiosarcomas as compared to other STS sites [15]. Thus, it is likely that our RT cohort included more malignant histologies and higher grade disease.…”
Section: Discussionmentioning
confidence: 99%